Предмет: Алгебра,
автор: katusha312k
(x-2)^4+(x-2)^2-2=0 .Решите уравнение
Ответы
Автор ответа:
0
(x-2)⁴+(x-2)²-2=0
Замена:
(х-2)² = t; t>0
t²+t-2=0
D=1²-4*1*(-2)=1+8=9=3²
t₁=(-1-3)/2=-2 -∅
t₂=(-1+3)/2=1
Обратная замена:
(x-2)²=1
x-2=1 или х-2=-1
х=1+2 х=-1+2
х=3 х=1
Ответ: х=1; х=3
Замена:
(х-2)² = t; t>0
t²+t-2=0
D=1²-4*1*(-2)=1+8=9=3²
t₁=(-1-3)/2=-2 -∅
t₂=(-1+3)/2=1
Обратная замена:
(x-2)²=1
x-2=1 или х-2=-1
х=1+2 х=-1+2
х=3 х=1
Ответ: х=1; х=3
Похожие вопросы
Предмет: Физика,
автор: ri722840
Предмет: Математика,
автор: mendibaevakamila3
Предмет: Английский язык,
автор: Sushka2021
Предмет: История,
автор: sashavodolaga
Предмет: Обществознание,
автор: semenovaksuha